Putative Identification of 47 Compounds from Jieyu Anshen Granule and Proposal of Pharmacopeia Quality‐Assessment Strategy Using TCM‐Specific Library with UHPLC‐Q‐Exactive‐Orbitrap‐MS - Xican Li; Jingyuan Zeng; Rongxin Cai; Chunhou Li; Xiaoshan Chen; Ban Chen; Xiaojun Zhao; Sunbal Khan (ChemistryOpen)
Abstract Jieyu Anshen Granule is a traditional Chinese medicine prescription used for depression and primarily comprises five herbal medicines: Zhizi, Chaihu, Zhigancao, Danggui, and Yuanzhi. This study established a traditional Chinese herbal medicine‐specific library using emerging ultra‐high‐performance liquid chromatography‐quadrupole‐orbitrap‐tandem mass spectrometry analysis. Through library comparison, the study has fulfilled isomers distinction. As a result, 47 compounds were simultaneously and putatively identified from Jieyu Anshen Granule, including 12 unexpected compounds and 35 expected compounds. The unexpected compounds comprised cyclocommunol, 5‐hydroxyflavone, tangeretin, 3,5,6,7,8,3’,4’‐heptemethoxyflavone, calycosin‐7‐O‐β‐D‐glucoside, 7,4’‐dihydroxyflavone, naringenin‐7‐O‐β‐D‐glucoside, matrine, betaine, jervine, alantolactone, and hypericin. Among the 35 expected compounds, saikosaponin A, saikosaponin D, glycyrrhizic acid, geniposide, ligustilide, and polygalaxanthone III were further investigated using a quantum chemistry approach. Based on these, an effective quality assessment strategy is proposed for the Pharmacopeia, involving the simultaneous analysis of glycyrrhizic acid, geniposide, ligustilide, polygalaxanthone III, saikosaponins A and D through ultra‐high‐performance liquid chromatography‐quadrupole‐orbitrap‐tandem mass spectrometry analysis. This strategy enables the detection of adulteration in relation to Zhizi, Chaihu, Zhigancao, Danggui, and Yuanzhi in Jieyu Anshen Granule. The findings of unexpected compounds will deepen the understanding of chemistry in Jieyu Anshen Granule.